Navigating hesitancy: Lived experiences of COVID-19 vaccine resistance and public health adaptations in the Philippines - Sypongco, Aileen G.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic has presented significant challenges to global public health, with vaccine hesitancy emerging as a major obstacle to achieving widespread immunity. This study examines the lived experiences of vaccine-resistant individuals in Negros Occidental, Philippines, to understand the underlying factors contributing to their hesitancy and how they navigate health protocols. Using a phenomenological approach, six unvaccinated participants were identified through snowball sampling in collaboration with local government health officials. Semi-structured interviews revealed three key themes: Navigating the Jab Maze, which explores concerns about vaccine safety and efficacy; Abiding by the Protocols for Unvaccinated Individuals, which highlights adherence to alternative preventive measures; and Embracing Health Concerns, which examines the role of personal beliefs, governance perceptions, and experiences of exclusion. Findings indicate that vaccine hesitancy stems from concerns about vaccines being experimental, personal convictions, and distrust in government policies. Despite their reluctance, participants adhered to public health measures, reflecting a complex balance between autonomy and collective responsibility. This study underscores the need for interdisciplinary strategies that integrate public health, social sciences, and policy-making to address vaccine hesitancy effectively. The findings provide insights for policymakers and healthcare practitioners in designing inclusive, trust-building interventions to enhance vaccine acceptance and public health outcomes.